The influence of tobacco exposure in color vision - Fabricio, Mariana Nunes; Lacerda, Eliza Maria da Costa Brito; Tomaz, Carlos Alberto Bezerra (Ciência e Natura, 2022)
Cigarette has about four thousand types of substances and its consumption is a risk factor for a variety of diseases, including neuro-ophthalmic disorders. This is a literature survey about the influence of smoking on color vision. Review of literature based in the Google Scholar research platforms, Scielo, Science Direct and the Bank of Dissertations and Theses of CAPES. Smoking articles, smoking, smoking and color vision and color vision in articles titles were adopted for inclusion criteria. Thus, 31 of which were sealed. In addition to cognitive changes, chronic use of tobacco can cause damage to retinal cells, impairing color vision, changes in tear protein patterns, adverse effects on the precorneal tear film and ocular surface. Metabolism is indirectly affected by means of the reduction of plasma levels of antioxidants and increasing the production of free radicals that impair eye health and blood flow in the ocular choroid. The chronic consumption of cigarettes causes changes in color vision / discrimination and such analysis alerts the harmful effects caused by the substances that compose it. In addition, psychophysical vision examination can be used as a screening test for intoxication processes that may be occurring in the subject.